Prevention and Management Intervention (PMI) of occupational ototoxic exposure in industrial perspective globally : A systematic review - Ainul Naqueah, Zainal Abidin; Mohd Shukri, Mohd Aris; Ailin, Razali; Norazura, Ismail (Universiti Putra Malaysia Press, 2022)
The World Health Organisation (WHO) has estimated an increasing number of occupational hearing loss. In Malaysia, there is high pervasiveness of hearing loss and hearing impairment among manufacturing workers. Ototoxicity Prevention and Management Intervention (PMI) is not yet established in the majority of countries, including Malaysia. This work aims to investigate the ototoxicity PMI from international guidelines and global reports. Method: Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 flow diagram was adopted for item selection. Two large data sets were used: (1) published, peer-reviewed articles obtained through two search strategies (PubMed and Web of Science); and (2) grey literature. Results: Sixteen items were identified and were categorised into a triad of approaches; exposure-based, knowledge-based, and clinical-based approaches. Conclusion: The way forward rises from this study suggested that an effective ototoxicity PMI is needed in occupational settings where ototoxic chemical (ototoxicants) exposure occurs. Therefore, more efforts should be geared toward ototoxicity PMI especially in developing countries.